From Narrow and Elongated to Proportional: Enhancing Cultivation through Shape Optimization in Rural Landscapes - Milati, Latifah Nur; Pujiriyani, Dwi Wulan; Sugiasih (BHUMI: Jurnal Agraria dan Pertanahan, 2025)
Abstract: This research aims to examine the transformation of narrow, elongated land in Triharjo Village into a more proportional shape through agricultural land consolidation activities. In the 1990s, the community self-organized, leading to a mismatch between the physical and legal conditions of the land. The government's initiative to accelerate systematic land registration through the Land Management and Policy Development Program in 2006-2007 also proved unable to accommodate this issue. The research method used is a qualitative approach with a case study. Data was collected through observation, document study, and in-depth interviews. Data analysis was conducted using the Miles and Huberman analysis method with 3 stages: data reduction, data presentation, and conclusion drawing. The research results show that the majority of agricultural land in Triharjo is less than 200 m² in size, with an unfavorable length-to-width ratio for cultivation. This condition stems from past inheritance processes that adhere to the principle of justice and the saying 'kabeh mangku dalan.' The implementation of the agricultural land consolidation program in 2019-2020 was able to achieve consistency between physical and legal conditions, provide proportional land parcel shapes for cultivation, and supply agricultural support infrastructure in the form of farm roads and irrigation channels. Keywords: Agricultural land consolidation, Disproportionate land, Inheritance, Land fragmentation.